Advances in liquid state theory - Henderson, D.; Pizio, O. (Condensed Matter Physics, 2013)
This special issue is a collection of papers coming from different research groups from different countries about recent advances in the area of theoretical description and computer simulations of fluids. All these papers, however, have been submitted to this particular journal with the dedication to Prof. Myroslav Holovko on the occasion of his 70th birthday.